2015
DOI: 10.3109/09638288.2015.1035457
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study: examining the effects and tolerability of structured dance intervention for individuals with multiple sclerosis

Abstract: Although structured dance has reported benefits in elderly populations and in individuals with cardiovascular and neurological impairments, there is virtually nothing known regarding dance in the MS population. This pilot salsa dance study shows that structured dance demonstrates promise of being well-tolerated, safe and effective at promoting physical activity in people with MS without increased fatigue. A 12-week study has been initiated to test the robustness of initial observations and further examine fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 32 publications
3
71
0
Order By: Relevance
“…In Project GEMS, the only identified barrier to participation was from potential participants unable to commit time. Compliance with the intervention was demonstrated in 13 studies via participant attendance at intervention sessions [35, 3740, 4247, 50, 52, 58], and in our case study, we also reported compliance via the number of completed exercise sessions. Participants reaction to outcome assessments were identified in 2 studies [49, 56], and issues identified included participants being unable to complete walking-based outcome assessments.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…In Project GEMS, the only identified barrier to participation was from potential participants unable to commit time. Compliance with the intervention was demonstrated in 13 studies via participant attendance at intervention sessions [35, 3740, 4247, 50, 52, 58], and in our case study, we also reported compliance via the number of completed exercise sessions. Participants reaction to outcome assessments were identified in 2 studies [49, 56], and issues identified included participants being unable to complete walking-based outcome assessments.…”
Section: Resultssupporting
confidence: 61%
“…The words feasibility and pilot were used in the title of 6 [35, 37, 47, 48, 51, 52] and 8 [7, 34, 3942, 44, 51] studies, respectively, and 23 [7, 3554, 57] studies indexed the word feasibility in the abstract, and 7 [7, 35, 4043, 48] studies included pilot in the abstract. One [35] study included feasibility in the key words, and one [52] study included pilot in the key words.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Statistically significant improvements were found from baseline to the end of the program on the Dynamic Gait Index (DGI), Timed Up and Preliminary efficacy data showed improved self-efficacy, as well as physical and mental health-related quality of life, but the specific effects of the dance intervention cannot be teased out. 31 …”
Section: Dance and Movement Therapymentioning
confidence: 99%